EXPANSION OF THE TERRITORY OF THE TRANS-KUBAN SETTLEMENT IN THE 40S OF THE 19TH CENTURY - Sapovalov, Sergej Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2023)
The establishment of new stanitsas (Cossack villages) as part of the Trans-Kuban (Zakubanye) settlement was caused by the needs of those who had already moved to the lands of the North-Western Caucasus and needed to be settled without military intervention to oust the mountaineers from their lands. The article aims to demonstrate the resettlement and colonization capacities of the Trans-Kuban settlement in the 1840s to understand the features of settlement and development of the lands of the North-Western Caucasus and the north-eastern coast of the Black Sea by the population of the Russian Empire. The application of the frontier theory allowed us to consider the Russian advance to the North-Western Caucasus not only as a set of military operations, but also as a process of external and internal relocation, the formation of new types of settlements, the establishment of various, including mutually beneficial ties between settlers and the local population. The study also applies retrospective, historical-genetic and systemic methods. The total number of migrants who needed permanent accommodation in the Trans-Kuban settlement was constantly growing, so the issue of allotting them plots of land was acute. One of the solutions to this situation was the construction of new settlements and stanitsas, which was complicated with two serious difficulties: the need for treasury funding and the actual absence of borders between the settlements of the Trans-Kuban settlement and Natukhai auls. Despite the existing difficulties, the leadership of the Black Sea Coastline set a course for the foundation of new strategically important fortified settlements. The completion of all the internal relocations started and the construction of new stanitsas in the 1840s allowed to significantly increase the number of the settled population; improve the defensive capabilities of settlements due to both careful planning of all necessary fortifications and an increase in the number of men; expand the area of land for the establishment of arable land, vegetable gardens, hayfields and pastures and create the necessary foundation for the subsequent food self-sufficiency of the population of the Trans-Kuban settlement.